Surgical Treatment for Profunda Femoris Artery Aneurysms: Five Case Reports - Kimihiro Igari; Toshifumi Kudo; Takahiro Toyofuku; Yoshinori Inoue (Case Reports in Vascular Medicine)
Profunda femoris artery aneurysm (PFAA) is an extremely rare entity, with most cases being asymptomatic, which makes obtaining an early diagnosis difficult. We herein report a case series of PFAA, in which more than half of the PFAAs, which presented with no clinical symptoms, were discovered incidentally. All PFAAs were treated surgically with aneurysmectomy with or without vascular reconstruction. In cases involving a patent superficial femoral artery (SFA), graft replacement of the profunda femoris artery (PFA) is not mandatory; however, preserving the blood flow of the PFA is necessary to maintain lower extremity perfusion in patients with occlusion of the SFA. Therefore, the treatment of PFAAs should include appropriate management of both the aneurysmectomy and graft replacement, if possible.